PIST (GOPC) modulates the oncogenic voltage-gated potassium channel KV10.1 - Herrmann, Solveig; Ninkovic, Milena; Kohl, Tobias; Pardo, Luis A. (Frontiers in Physiology, 2013)
Although crucial for their correct function, the mechanisms controlling surface expression of ion channels are poorly understood. In the case of the voltage-gated potassium channel KV10.1,this is determinant not only for its physiological function in brain, but also for its pathophysiology in tumors and possible use as a therapeutic target. The Golgi resident protein PIST binds several membrane proteins, thereby modulating their expression. Here we describe a PDZ domain-mediated interaction of KV10.1and PIST, which enhances surface levels ofKV10.1. The functional, but not the physical interaction of both proteins is dependent on the coiled-coil and PDZ domains of PIST; insertion of eight amino acids in the coiled-coil domain to render the neural form of PIST (nPIST) and the corresponding short isoform in an as-of-yet unknown form abolishes the effect. In addition, two new isoforms of PIST (sPIST and nsPIST) lacking nearly the complete PDZ domain were cloned and shown to be ubiquitously expressed. PIST and KV10.1 co-precipitate from native and expression systems. nPISTalso showed interaction, but did not alter the functional expression of the channel. We could not document physical interaction betweenKV10.1 and sPIST, but it reduced KV10.1 functional expression in a dominant-negative manner. nsPIST showed weak physical interaction and no functional effect on KV10.1. We propose these isoforms to work as modulators of PIST function via regulating the binding on interaction partners.